The signal for the termination of protein synthesis in procaryotes. - Brown, C M (1990)
The sequences around the stop codons of 862 Escherichia coli genes have been analysed to identify any additional features which contribute to the signal for the termination of protein synthesis. Highly significant deviations from the expected nucleotide distribution were observed, both before and after the stop codon. Immediately prior to UAA stop codons in E. coli there is a preference for codons of the form NAR (any base, adenine, purine), and in particular those that code for glutamine or the basic amino acids. In contrast, codons for threonine or branched nonpolar amino acids were under-represented. Uridine was over-represented in the nucleotide position immediately following all three stop codons, whereas adenine and cytosine were under-represented. This pattern is accentuated in highly expressed genes, but is not as marked in either lowly expressed genes or those that terminate in UAG, the codon specifically recognised by polypeptide chain release factor-1. These observations suggest that for the efficient termination of protein synthesis in E. coli, the 'stop signal' may be a tetranucleotide, rather than simply a tri-nucleotide codon, and that polypeptide chain release factor-2 recognises this extended signal. The sequence following stop codons was analysed in genes from several other procaryotes and bacteriophages. Salmonella typhimurium, Bacillus subtilis, bacteriophages and the methanogenic archaebacteria showed a similar bias to E. coli.